Entitlement, rules, coordination, club, market and hierarchy: General budget support practice and theory ; implications of results of the joint evaluation of general budget support - Michael Hubbard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The paper discusses implications for practice and theory of the recently completed Joint Evaluation of General Budget Support 2004-06 based on case studies in Burkina Faso, Malawi, Mozambique, Nicaragua, Rwanda, Uganda and Vietnam. The paper first looks at the extent to which general budget support, on the evidence of the evaluation, stands up to common criticisms of the effects of aid on government in low income, aid dependent countries. Allowing for much caution owing to the short period of partnership general budget support (PGBS) programmes in some countries, the finding is that there are small but positive impacts (notably reducing unnecessary transaction costs and increasing discretion of government—thereby raising allocative and operational efficiency). Net benefits are generally greater where PGBS programmes are longer established. Areas of uncertainty regarding future effects are its uncertain overall contribution to the private sector and growth, its vulnerability to changes in political relations, and the limitations to raising `pro-poor expenditure'—the main tool it has used to leverage increases in health and education spending; long term improvements in access and quality of public services will rely on better planning, budgeting and services management. The paper then considers how the evaluation results affect the way that PGBS is understood in theory: (i) it first suggests that PGBS raises entitlements (by increasing confidence that there will be continuing flows of budget support) which encourages policy development and stable donor-government collaboration structures, to which other shorter term aid arrangements gravitate, thereby reducing previous coordination failures; (ii) relations in organizations are then identified on a spectrum from market through club to hierarchy. Applied to PGBS coordination structures this suggests they are aspirant clubs, with hierarchical features strongest where PGBS is least established, and club features stronger where government is more capable and assertive; (iii) entitlements are accompanied by rules which attempt to raise positive incentive effects of the entitlement and reduce its negative incentive effects. In PGBS arrangements rules vary from hierarchical (e.g., prior actions), through club oriented (e.g., assessment on medium term trends) to market oriented (performance payments related to achievement on specific indicators). The analysis of rules in relation to PGBS incentives and operating environments (on a spectrum from rigid/uncertain to flexible/predictable) concludes that fine tuning rules in rigid/uncertain operating environments is counterproductive. Integrating PGBS performance assessment frameworks (PAFs) into government plans and monitoring systems will serve to unify rules. – aid ; budget support ; entitlement ; rules ; club ; market ; coordination
Keywords: H41; H50; O10; O20; 330